Synergistic 3D π–π networks enforce persistent foldamer configuration with tunable full-color circularly polarized luminescence - Hu, Hao; Zhang, Qiangsheng; Wu, Ziyan; Liu, Hongtao; Xie, Jialin; Wen, Zhenchang; Chi, Weijie; Li, Jianwei; Jia, Chunman (Springer Nature, 2026)
Achieving molecular chirality with enantiostability in purely π-conjugated foldamers remains a substantial challenge due to inherently weak π-π stacking interactions and facile racemization. Herein, we introduce a novel design strategy employing synergistic intramolecular 3D π–π stacking networks within a 1,8-diarylnaphthalene framework, enabling foldamers to exhibit extraordinary configurational stability. A systematic series of quinoxaline- and phenazine-based foldamers incorporating carbazole (CZ) and diphenylamine (DPA) donors were synthesized, with chiral configurations stabilized through complementary face-to-face and laterally offset π–π stacking interactions. Single-crystal X-ray analyses and computational studies confirmed the formation of complex intramolecular π-networks, providing exceptional racemization barriers (ΔG‡ up to 26.06 kcal mol-1), exceeding conventional atropisomers. Additionally, the modular donor-acceptor design facilitates full-color circularly polarized luminescence (469–684 nm), maintaining high dissymmetry factors (|glum | > 10-3) across solution and solid-state environments. This work establishes a generalizable principle for constructing chiral foldamers with enantiostability and tunable optical properties through tailored 3D aromatic interactions, offering significant advances in chiral optoelectronics and responsive materials.